Pengaruh Jus Belimbing (Averhoa Carambola Linn) Terhadap Tekanan Darah Penderita Hipertensi di Posyandu Lansia Bahagia Puskesmas Mulyorejo - Layli, Alvia Nur; Purwaningsih, Eka (Infokes, 2018)
Hypertension is a common public health problem in developing countries and the second highest cause of death in Indonesia. Sweet starfruit (Averhoa Carambola Linn) many contain Potassium. According to the initial survey, 10 respondents of elderly with hypertension are obtained. The aim of this study is to analyze the difference in terms of blood pressure average by giving sweet starfruit juice towards the respondents. This study is Quasi experimental research using the approach of one group pre-post test design. The Population of all hypertension patients in Integrated Services Post (Posyandu) for elderly is 21 respondents with sample of 10 respondents. The experiment was conducted in August 2017. The patient gived a sweet starfruit juice as much as 180 gr/day. Sampling method use is purposive sampling. The data are collected using interview, questionnaire of nutrition and measure of blood pressure. The research instruments are sphygonamometer, stationery, blender, measuring cup, spoon, and sweet starfruit. The data are analyzed using Paired T-Test. The result shows that blood pressure on 8 respondents (80%) before intervention is classified as 1 degree hypertension and the blood pressure on 6 respondents (60%) after intervention is classified as prehypertension. The results of SPSS Paired T-Test with (p = 0,003) it means there were difference before and after of blood pressure with sweet starfruit juice in patients of hypertension . Significant impact of giving sweet starfruit juice in decreasing blood pressure of hypertension patients is found within this study. Based on the results of the study, it is recommended for patients with hypertension to consume of sweet starfruit juice there are no pharmacological to lowering blood pressure.